2014
DOI: 10.5114/aoms.2014.47825
|View full text |Cite
|
Sign up to set email alerts
|

Indications requiring preoperative magnetic resonance imaging before knee arthroscopy

Abstract: IntroductionKnee arthroscopy knee is gold standard in diagnosis and simultaneous treatment of knee disorders. But most patients undergo magnetic resonance imaging (MRI) before arthroscopy, although MRI results are not always consistent with arthroscopic findings. This raises the question in which suspected diagnoses MRI really has influence on diagnosis and consecutive surgical therapy.Material and methodsPreoperative MRI of 330 patients with knee disorders were compared with arthroscopic findings. The MRI wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Arthroscopy allows direct visualization of all intra-articular structures and thus provides a high level of accuracy for both diagnosis and treatment, which makes arthroscopy the gold standard for evaluation of internal disorders and other lesions of the knee 7 . However, arthroscopy constitutes a relatively expensive and invasive examination 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Arthroscopy allows direct visualization of all intra-articular structures and thus provides a high level of accuracy for both diagnosis and treatment, which makes arthroscopy the gold standard for evaluation of internal disorders and other lesions of the knee 7 . However, arthroscopy constitutes a relatively expensive and invasive examination 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Chambers et al 13 compared the MRI meniscal images with arthroscopy, finding that MRI scanning was 90.5% sensitive, 89.5% specific and 90.1% accurate. Roßbach et al 14 found sensitivity/specificity of 58/93% for anterior horn, 94/46% for posterior horn of medial meniscus and 71/81% for anterior and 62/82% for posterior horn of lateral meniscus. The specificity of conventional MRI can be improved by employing at least two T2-weighted sequences, but this still leaves a shortfall in sensitivity and if MRI is contraindicated, computed tomography arthrography seems a promising alternative.…”
Section: Introductionmentioning
confidence: 98%
“…Magnetic resonance imaging (MRI) of knee joints aids in the detection of the site and degree ACL injury [3]. However, arthroscopy remains the gold standard for assessment of internal derangement of the knee joint with the limitation of being an expensive and invasive procedure [4]. The ACL possesses a unique diagonal course extending from the inner surface of the lateral femoral condyle and attaching to a fossa in front and lateral to the anterior tibial spine [5].…”
Section: Introductionmentioning
confidence: 99%